2020
DOI: 10.1021/acs.energyfuels.9b04498
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Methane Adsorption on Shale over Wide Pressure and Temperature Ranges: Implications for Gas-in-Place Estimation

Abstract: Methane adsorption experiments over wide ranges of pressure (up to 30 MPa) and temperature (30–120 °C) were performed using a gravimetric method on the Longmaxi shale collected from the northeast boundary of Sichuan Basin, China. Organic geochemical analyses, shale composition determination, and porosity tests were also conducted. The experimental supercritical methane excess adsorption isotherms at different temperatures initially increase and then decrease with increasing pressure, giving a maximum excess ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 70 publications
2
56
0
Order By: Relevance
“…Developed countries such as the United States, China, and Europe have already addressed numerous apprehensions about the status and hurdles. They have also recommended practices for unconventional natural gas resource exploitation and development to solve the energy crisis via different enhanced oil and gas recovery pathways and smart drilling techniques. Figure shows the status of production of unconventional natural gas from coalbed methane, shale gas, and tight gas around the globe. , Among the developing countries, Pakistan needs considerable natural gas in order to develop its infrastructure. Surging energy consumption in different industry sectors such as power-generating plants and cement industry has also increased natural gas consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Developed countries such as the United States, China, and Europe have already addressed numerous apprehensions about the status and hurdles. They have also recommended practices for unconventional natural gas resource exploitation and development to solve the energy crisis via different enhanced oil and gas recovery pathways and smart drilling techniques. Figure shows the status of production of unconventional natural gas from coalbed methane, shale gas, and tight gas around the globe. , Among the developing countries, Pakistan needs considerable natural gas in order to develop its infrastructure. Surging energy consumption in different industry sectors such as power-generating plants and cement industry has also increased natural gas consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular simulation found that increasing temperature reduces the isosteric heats of adsorption, 43 while methane adsorption sites tend to shift from low-energy sites to high-energy sites, resulting in a decrease in methane adsorption. 36,43 Langmuir pressure P L is a temperature-dependent parameter related to the enthalpy of adsorption, and the relationship between P L and temperature can be expressed as 86,87…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that an increase of 50 °C leads to a 23.05% reduction in the maximum adsorption capacity. The molecular simulation found that increasing temperature reduces the isosteric heats of adsorption, while methane adsorption sites tend to shift from low-energy sites to high-energy sites, resulting in a decrease in methane adsorption. , Langmuir pressure P L is a temperature-dependent parameter related to the enthalpy of adsorption, and the relationship between P L and temperature can be expressed as , where T is the temperature in K; Δ H is the adsorption enthalpy, J/mol; Δ S 0 is the standard adsorption entropy, J/mol/K; R is the ideal gas constant of 8.3145 J/mol/K; and P 0 is the atmospheric pressure of 0.101 MPa. The negative linear relationship between ln P L and 1/ T can be observed in Figure a, which indicates that the higher the temperature, the higher the P L .…”
Section: Resultsmentioning
confidence: 99%
“…The shale samples were taken from the Silurian Longmaxi Formation in the Sichuan Basin, China, and the adsorption isotherms of methane were measured by a gravimetric approach within the pressure range of 0−30 MPa and temperature range of 303− 393 K. The total organic carbon (TOC) content in this sample was 3.65%, and the detailed information of other physical parameters can be found in the original publication. 48 Here, only the adsorption isotherms at different temperatures have been displayed (Figure 2). These data have been substituted into eq 4, and the parameters of the adsorption model were obtained by the global fitting method, as shown in Table 1.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%